Problematika Layanan Bimbingan dan Konseling Di Sekolah Dasar - Rahmi, Tysa Sufia; Mudjiran, Mudjiran; Neviyarni S., Neviyarni S.; Nirwana, Herman (MODELING: Jurnal Program Studi PGMI, 2023)
This study is motivated by the problems found by elementary school teachers during the implementation of guidance and counseling services in elementary schools. This study aims to look at guidance and counseling services in elementary schools and describe the problems experienced by teachers in their implementation and the solutions that can be given to solve these problems. This research uses descriptive qualitative research. The researcher determined SDN 13 Parit Putus as the research location and the teacher as the research subject. Researchers collected research data through in-depth interviews, observations, and documentation of teachers at SDN 13 Parit Putus. The results of the study show that the problems of guidance and counseling services in elementary schools are the absence of guidance and counseling teachers, the absence of training on guidance and counseling services, teachers do not have an understanding of designing administration, and inadequate guidance and counseling service facilities at SDN 13 Parit Putus. The solutions provided by researchers are to procure counseling teachers in elementary schools, provide training through gifted counselors, complete the administration of counseling services, and facilitate the needs of guidance and counseling.